Exploring What Happens When Students and a Pre-Service Teacher Use Student-Centered Learning to Foster a Democratic Classroom (2024)
This action-research aimed at exploring what happens when students and a pre-service teacher use Student-centered Learning to foster a Democratic Classroom. It was conducted in a public school located in Rionegro, Antioquia, Colombia with 26 seventh graders. Action strategies included involvement and cooperation of students in making decisions about the assessment procedures and activities of the class. Data gathering instruments consisted of questionnaires, mini surveys, a focus group, and pre-service teacher’s journals. Findings revealed that the students gained awareness about the decisions they were making and the effects of giving feedback and that the pre-service teacher questioned her role as a teacher and as an evaluator in a democratic classroom.